Music Perception and Music-Related Quality of Life in Adult Cochlear Implant Users: Exploring the Need for Music Rehabilitation - ÇİPRUT, AYŞE AYÇA (My University, 2024)
Objectives: Cochlear implant (CI) users face difficulties in accurately perceiving basic musical elements such as pitch, melody, and timbre. Music significantly affects the quality of life (QoL) of CI users. Individually and culturally influenced music perception exceeds psychophysical measures in capturing the subjective music enjoyment of CI users. Understanding the music perception, enjoyment, and habits of CI users is crucial for approaches to improve music-related QoL (MuRQoL). Therefore, this study aims to investigate music perception skills, experiences, and participation in music activities in a large group of adult CI users, and to understand the importance of these factors and their impact on QoL of CI users. Design: This study included 214 CI recipients with diverse auditory experiences who were aged between 18 and 65 years and were unilateral, bimodal, or bilateral users for at least 1 year and 193 normal hearing (NH) controls. All participants completed the information forms and the MuRQoL questionnaire. To assess the impact of music on QoL and identify personalized rehabilitation needs, the scores for each question in both parts of the questionnaire were intersected on a matrix. Data were presented in detail for the CI group and compared between CI and NH groups. Results: A statistically significant difference was found between the matched CI and NH groups in favor of the NH group in terms of music perception and music engagement. Participants who received music education at any point in their lives had significantly higher MuRQoL questionnaire scores. There was no significant relationship found between the duration of auditory rehabilitation, pre-CI hearing aid usage, music listening modality, and MuRQoL questionnaire scores. Unilateral CI users had significantly lower scores in music perception and music engagement subsections compared with bimodal and bilateral CI users. Also, it was found that music had a strong negative impact on QoL in 67/214 of the CI users. Conclusions: Although CI users scored significantly lower than NH individuals on the first part of the questionnaire, which asked about musical skills, enjoyment, and participation in musical activities, findings suggest that CI users value music and music enjoyment just as much. The study reveals the influence of factors such as education level, age, music education, type of hearing loss and auditory rehabilitation on music perception, music enjoyment, and participation in music activities through self-report. The results indicate that for many CI users, music has a strong negative impact on QoL, highlighting the need for personalized music interventions, the inclusion of self-report questionnaires, and music perception tests in clinical evaluations.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Otolaryngology; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Clinical Medicine (Med); Clinical Medicine; Otorhinolaryngology; Konuşma ve İşitme; Speech and Hearing; Cochlear implants; Music perception; Music rehabilitation; music-related quality of life